Produksi Bioetanol Dari Mikroalga Chlorella sp. Dengan Variasi Konsentrasi H2SO4 - Wulandari, Zarah Ayu; Muria, Sri Rezeki; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Microalgae is one type of raw material that has the potential to be used as bioethanol, because it has the ability to grow in a relatively short time, can be cultivated in a limited area, and several types of microalgae have a high carbohydrate content. The purpose of this study was to determine the effect of variations in the concentration of H2SO4 on bioethanol produced. The substrate used in the fermentation process in this study was microalgae Chlorella sp. obtained from microalgae cultivation by fed-batch in oil palm liquid waste media. The preliminary stage carried out in this research is the preparation of the microalgae raw material Chlorella sp. to form a powder. Microalgae powder was used as a substrate and hydrolyzed with variations in the concentration of H2SO4 3%, 4%, and 5%. The hydrolysis solution was then fermented using Saccaromyces cerevisiae with a concentration of 10% Saccaromyces cerevisiae inoculum volume. The results showed that 4% (v/v) H2SO4 produced the highest glucose concentration, which was 37,87 mg/mL with the resulting bioethanol concentration of 15,78 mg/mL. Keywords: bioethanol, H2SO4, microalgae, Saccaromyces cerevisiae